A compend of the Institutes of the Christian religion - Calvin, John 1509-1564; Kerr, Hugh Thompson (Philadelphia, PA Presbyterian Board of Christian Education, 1939)
Includes index.
Keywords: Calvin, John -- 1509-1564.; Church history -- Reformation -- writings